Competitive binding between DDX21 and SIRT7 enhances NAT10-mediated ac4C modification to promote colorectal cancer metastasis and angiogenesis– DDX21 promotes colorectal cancer metastasis - Angxi Song; Bowen Liu; Wenjing Li; Bingyuan Chen; Pengkun Gui; Hao Zhang; Can Zhu; Yixin Xu; Tao Jiang; Jun Song (Cell Death and Disease)
Abstract DExD- box helicase 21 (DDX21) is overexpressed in colorectal cancer (CRC) and is positively correlated with poor prognosis and the malignant phenotype of CRC. Functional characterization indicated that DDX21 promotes CRC metastasis and angiogenesis both in vitro and in vivo. N-acetyltransferase 10 (NAT10) is a key regulator of the N4-acetylcytidine (ac4C) modification of mRNA, regulating the stabilization of mRNA via ac4C modification. Here, we identified that DDX21 competitive binding with sirtuin 7 (SIRT7), inducing the overexpression of NAT10. Furthermore, DDX21 upregulates NAT10 expression to enhance ac4C modification and the stability of ATAD2, SOX4 and SNX5 mRNAs, which mediate CRC metastasis and angiogenesis. Overall, the present study revealed a mechanism of DDX21/NAT10-mediated mRNA stability in CRC, laying the foundation for the use of DDX21 as a therapeutic target to overcome metastasis and angiogenesis in CRC. DDX21 competitive binding with sirtuin 7 (SIRT7), inducing the overexpression of NAT10. Furthermore, DDX21 upregulates NAT10 expression to enhance ac4C modification and the stability of ATAD2, SOX4 and SNX5 mRNAs, which mediate CRC metastasis and angiogenesis.